With great structure comes great functionality: Understanding and emulating spider silk. Issue 1 (18th December 2014) - Brown, Cameron P.; Whaite, Alessandra D.; MacLeod, Jennifer M.; Macdonald, Joanne; Rosei, Federico
Abstract